Analysis of the Development of Social Interaction and Independence of Children with Autism at Permata Diakoni Pematangsiantar - Lastiurida Siburian; Asister Fernando Siagian; Natalina Purba (International journal of technology and education research, 2026)
This study aims to analyze the development of social interaction and independence in children with autism at Permata Diakoni. The focus of the study was on one subject, identified as MS, who experienced difficulties in communication, social interaction, and self-development skills. The study used a qualitative approach with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña using NVivo version 15. Data validity was tested through source triangulation and time triangulation. The results showed that the development of the subject's social interaction began to be evident through increased responsiveness to calls, eye contact, and the ability to follow simple instructions. In terms of independence, the subject showed progress in self-feeding, following daily routines, and completing simple tasks with minimal direction. However, the subject still experienced difficulties in spontaneous social initiative, emotional regulation, and several self-development skills that required assistance. Supporting factors for development included a structured learning environment, consistent teacher guidance, and repeated positive reinforcement. It was concluded that a supportive and structured educational environment plays a crucial role in gradually improving the social interaction and independence of children with autism.